A Systematic Review of Iran's Medicinal Plants With Anticancer Effects. (April 2016) - Asadi-Samani, Majid; Kooti, Wesam; Aslani, Elahe; Shirzad, Hedayatollah
Increase in cases of various cancers has encouraged the researchers to discover novel, more effective drugs from plant sources. This study is a review of medicinal plants in Iran with already investigated anticancer effects on various cell lines. Thirty-six medicinal plants alongside their products with anticancer effects as well as the most important plant compounds responsible for the plants' anticancer effect were introduced. Phenolic and alkaloid compounds were demonstrated to have anticancer effects on various cancers in most studies. The plants and their active compounds exerted anticancer effects by removing free radicals and antioxidant effects, cell cycle arrest, induction of apoptosis, and inhibition of angiogenesis. The investigated plants in Iran contain the compounds that are able to contribute effectively to fighting cancer cells. Therefore, the extract and active compounds of the medicinal plants introduced in this review article could open a way to conduct clinical trials on cancer and greatly help researchers and pharmacists develop new anticancer drugs.